Punicalagin Attenuates Disturbed Flow-Induced Vascular Dysfunction by Inhibiting Force-Specific Activation of Smad1/5 - Anwaier, Gulinigaer; Lian, Guan; Ma, Gui-Zhi; Shen, Wan-Li; Lee, Chih-I; Lee, Pei-Ling; Chang, Zhan-Ying; Wang, Yun-Xia; Tian, Xiao-Yu; Gao, Xiao-Li; Chiu, Jeng-Jiann; Qi, Rong (Frontiers in Cell and Developmental Biology, 2021)
Background Pathophysiological vascular remodeling in response to disturbed flow with low and oscillatory shear stress (OSS) plays important roles in atherosclerosis progression. Pomegranate extraction (PE) was reported having anti-atherogenic effects. However, whether it can exert a beneficial effect against disturbed flow-induced pathophysiological vascular remodeling to inhibit atherosclerosis remains unclear. The present study aims at investigating the anti-atherogenic effects of pomegranate peel polyphenols (PPP) extraction and its purified compound punicalagin (PU), as well as their protective effects on disturbed flow-induced vascular dysfunction and their underlying molecular mechanisms. Methods The anti-atherogenic effects of PPP/PU were examined on low-density lipoprotein receptor knockout mice fed with a high fat diet. The vaso-protective effects of PPP/PU were examined in rat aortas using myograph assay. A combination of in vivo experiments on rats and in vitro flow system with human endothelial cells (ECs) was used to investigate the pharmacological actions of PPP/PU on EC dysfunction induced by disturbed flow. In addition, the effects of PPP/PU on vascular smooth muscle cell (VSMC) dysfunction were also examined. Results PU is the effective component in PPP against atherosclerosis. PPP/PU evoked endothelium-dependent relaxation in rat aortas. PPP/PU inhibited the activation of Smad1/5 in the EC layers at post-stenotic regions of rat aortas exposed to disturbed flow with OSS. PPP/PU suppressed OSS-induced expression of cell cycle regulatory and pro-inflammatory genes in ECs. Moreover, PPP/PU inhibited inflammation-induced VSMC dysfunction. Conclusions PPP/PU protect against OSS-induced vascular remodeling through inhibiting force-specific activation of Smad1/5 in ECs and this mechanism contributes to their anti-atherogenic effects.